Implications of differentiated care for successful ART scale‐up in a concentrated HIV epidemic in Yangon, Myanmar. (21st July 2017) - Mesic, Anita; Fontaine, Julie; Aye, Theingy; Greig, Jane; Thwe, Thin Thin; Moretó‐Planas, Laura; Kliesckova, Jarmila; Khin, Khin; Zarkua, Nana; Gonzalez, Lucia; Guillergan, Erwin Lloyd; O'Brien, Daniel P.
Abstract: Introduction : National AIDS Programme in Myanmar has made significant progress in scaling up antiretroviral treatment (ART) services and recognizes the importance of differentiated care for people living with HIV. Indeed, long centred around the hospital and reliant on physicians, the country's HIV response is undergoing a process of successful decentralization with HIV care increasingly being integrated into other health services as part of a systematic effort to expand access to HIV treatment. This study describes implementation of differentiated care in Médecins Sans Frontières (MSF)‐supported programmes and reports its outcomes. Methods : A descriptive cohort analysis of adult patients on antiretroviral treatment was performed. We assessed stability of patients as of 31 December 2014 and introduced an intervention of reduced frequency of physicians' consultations for stable patients, and fast tract ART refills. We measured a number of saved physician's visits as the result of this intervention. Main outcomes, remained under care, death, lost to follow up, treatment failure, were assessed on 31 December 2015 and reported as rates for different stable groups. Results : On 31 December 2014, our programme counted 16, 272 adult patients enrolled in HIV care, of whom 80.34% were stable. The model allowed for an increase in the average number of patients one medical team could care for – from 745 patients in 2011 to 1, 627 in 2014 – and, thus, a reduction in the number of teams needed. An assessment of stable patients enrolled on ART one year after the implementation of the new model revealed excellent outcomes, aggregated for stable patients as 98.7% remaining in care, 0.4% dead, 0.8% lost to follow‐up, 0.8% clinical treatment failure and 5.8% with immunological treatment failure. Conclusions : Implementation of a differentiated model reduced the number of visits between stable clients and physicians, reduced the medical resources required for treatment and enabled integrated treatment of the main co‐morbidities. We hope that these findings will encourage other stakeholders to implement innovative models of HIV care in Myanmar, further expediting the scale up of ART services, the decentralization of treatment and the integration of care for the main HIV co‐morbidities in this context.